Water inflatable unmanned ship based on artificial intelligence - CHEN KANGZHI; ZHU MINGJIAN; HUANG XIAOFU; XIAO DONG; MAO DEJUN; MAI HAOPING; YANG HEE-GUN; WU XIANHENG; HE JIAJIE; HUANG JUNYU; HUANG JINMING; LI HANG; et al. (2023)
The invention discloses a water inflatable unmanned ship based on artificial intelligence. The water inflatable unmanned ship comprises an intelligent inflatable ship body (1), a communication module (2) and an intelligent control module (3). The intelligent inflatable boat body (1) comprises a boat body (4), an inflatable cabin module (5), a ballast module (6) and a performance module (7); the inflation cabin module (5) can change provided buoyancy through inflation and exhaust so as to adjust the sinking and floating state of the ship body (4), the ballast module (6) is matched with the inflation cabin module (5) to adjust the sinking and floating state of the ship body (4), the ballast module (6) comprises a plurality of ballast units, the ballast units can be adjusted, and the ballast units can be used for adjusting the sinking and floating state of the ship body (4). The performance module (7) is arranged on the ship body (4) and used for lamplight and fountain performance. When the intelligent inflatabl